The Practice of Pancasila Values in the Implementation of Tolerance Among Religious Communities for Students of UIN Mahmud Yunus Batusangkar in Places of Worship in the City of Padang Related to the Letter (QS. Al-Hujurat: 13) and Tafsir Al-Muyassar - Mahmuda; Ridianto (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2025)
Pancasila is the foundation of the Indonesian nation that has a function in social life. Pancasila as a tool to unite the nation, the personality of the nation, the outlook on life of the nation, the source of all sources of law and sources of knowledge in Indonesia. Diversity in society is one thing that is very important for social life in the Unitary State of the Republic of Indonesia. As in Pancasila, the third principle which reads "Indonesian Diversity", this is also agreed upon in the Qur'an, surah al-Hujurat verse 13 which discusses the meaning of diversity from the values ​​of Pancasila contained therein. However, seeing the facts now, there are many phenomena that lose the meaning of the values ​​of Pancasila. Therefore, it is very important to instill the values ​​of diversity from the values ​​of the third principle to the people of Indonesia. The aims of this research are: (1) To find out the values ​​of diversity in Pancasila from the perspective of the Qur'an, Surah Al-Hujurat, verse 13, (2) to find out the relevance of the values ​​of diversity in Pancasila from the perspective of the Qur'an, Surah Al-Hujurat, verse 13 with contemporary social life. Pancasila adalah dasar bangsa Indonesia yang memiliki fungsi dalam kehidupan bermasyarakat. Pancasila sebagai alat pemersatu bangsa, kepribadian bangsa, pandangan hidup bangsa, sumber dari segala sumber hukum dan sumber ilmu pengetahuan di Indonesia. Keragaman dalam masyarakat merupakan satu hal yang sangat penting bagi kehidupan bermasyarakat di Negara Kesatuan Republik Indonesia. Sebagaimana dalam Pancasila, sila ketiga yang berbunyi “Keragaman Indonesia”, hal ini diamini pula dalam Al-Qur’an surah Al-Hujurat ayat 13 yang membahas tentang makna keragaman dari nilai Pancasila yang ada di dalamnya. Akan tetapi, melihat fakta yang ada sekarang banyaknya fenomena yang kehilangan makna dari nilai Pancasila. Karena itu sangat penting untuk menanamkan asyara nilai-nilai keragaman dari nilai sila ketiga kepada asyarakat Indonesia. Adapun tujuan dalam penelitian ini adalah: (1) Mengetahui nilai-nilai keragaman pada Pancasila perspektif al-Qur’an surah al-Hujurat ayat 13, (2) mengetahui relevansi nilai-nilai keragaman pada Pancasila perspektif al- Qur’an surah al-Hujurat ayat 13 dengan kehidupan sosial masa kini.